2013
DOI: 10.1152/ajplung.00101.2012
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 receptor α2-arginase 2 pathway mediates IL-13-induced pulmonary hypertension

Abstract: Lee CG. IL-13 receptor ␣ 2-arginase 2 pathway mediates IL-13-induced pulmonary hypertension. Am J Physiol Lung Cell Mol Physiol 304: L112-L124, 2013. First published November 2, 2012; doi:10.1152/ajplung.00101.2012.-Although previous literature suggests that interleukin (IL)-13, a T-helper type 2 cell effector cytokine, might be involved in the pathogenesis of pulmonary hypertension (PH), direct proof is lacking. Furthermore, a potential mechanism underlying IL-13-induced PH has never been explored. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 49 publications
(59 reference statements)
2
46
1
Order By: Relevance
“…Munitz and colleagues (31) also found up-regulation of IL-13 in BAL during OVA-induced acute lung inflammation. A recent study with IL-13 transgenic mice showed that IL-13 overexpression can induce PH and vascular remodeling via arginase 2 and nitric oxide synthase 3 (33). Our current data do not support a role for IL-13 in inducing pulmonary vascular remodeling, and IL-13 is not likely vital to eosinophil recruitment.…”
Section: Discussioncontrasting
confidence: 93%
“…Munitz and colleagues (31) also found up-regulation of IL-13 in BAL during OVA-induced acute lung inflammation. A recent study with IL-13 transgenic mice showed that IL-13 overexpression can induce PH and vascular remodeling via arginase 2 and nitric oxide synthase 3 (33). Our current data do not support a role for IL-13 in inducing pulmonary vascular remodeling, and IL-13 is not likely vital to eosinophil recruitment.…”
Section: Discussioncontrasting
confidence: 93%
“…Other studies have shown that dysregulation of IL-13 signaling is present in human PAH, although whether IL-13 is pro-or antiproliferative remains unclear. 36,40,41 Consequent to these findings, we found evidence of enhanced PH in S. mansoniinfected mice lacking IL-13Rα2, suggesting that IL-13 signaling is an important mediator of the granulomatous and vascular response to schistosomiasis infection. 37 Thus, the IL-13 ligand and receptors may serve as novel biomarkers in PH and potential targets for receptor-directed therapeutic agents.…”
supporting
confidence: 71%
“…Vascular SMCs and ECs isolated from these mice express only arginase II, whereas alveolar macrophages express both arginase isoforms. Deletion of arginase II in these animals decreased medial wall thickening of the pulmonary arteries and reduced the frequency of neovascularization of small pulmonary arteries (5).…”
Section: Discussionmentioning
confidence: 83%